Adipose tissue macrophages and their role in obesity-associated insulin resistance: an overview of the complex dynamics at play. Issue 3 (9th March 2023) - Guria, Suktara; Hoory, Anupama; Das, Snehasis; Chattopadhyay, Dipanjan; Mukherjee, Sutapa
Abstract: Obesity, a major global health concern, is characterized by serious imbalance between energy intake and expenditure leading to excess accumulation of fat in adipose tissue (AT). A state of chronic low-grade AT inflammation is prevalent during obesity. The adipose tissue macrophages (ATM) with astounding heterogeneity and complex regulation play a decisive role in mediating obesity-induced insulin resistance. Adipose-derived macrophages were broadly classified as proinflammatory M1 and anti-inflammatory M2 subtypes but recent reports have proclaimed several novel and intermediate profiles, which are crucial in understanding the dynamics of macrophage phenotypes during development of obesity. Lipid-laden hypertrophic adipocytes release various chemotactic signals that aggravate macrophage infiltration into AT skewing toward mostly proinflammatory status. The ratio of M1-like to M2-like macrophages is increased substantially resulting in copious secretion of proinflammatory mediators such as TNFα, IL-6, IL-1β, MCP-1, fetuin-A (FetA), etc. further worsening insulin resistance. Several AT-derived factors could influence ATM content and activation. Apart from being detrimental, ATM exerts beneficial effects during obesity. Recent studies have highlighted the prime role of AT-resident macrophage subpopulations in not only effective clearance of excess fat and dying adipocytes but also in controlling vascular integrity, adipocyte secretions, and fibrosis within obese AT. The role of ATM subpopulations as friend or foe is determined by an intricate interplay of such factors arising within hyperlipidemic microenvironment of obese AT. The present review article highlights some of the key research advances in ATM function and regulation, and appreciates the complex dynamics of ATM in the pathophysiologic scenario of obesity-associated insulin resistance.